A study of the relationship between solar activities and earthquakes / Indriani Sukma - Indriani , Sukma (2017)
The Sun is a prime source of energy while the Earth is the third planet near to the Sun and the only planet that has very large seismic activity. The solar wind interacts with the ionospheric currents and affects the Earth magnetic field causing a geomagnetic storm. Therefore, the study on the correlation between solar activity and earthquake is very important. The geomagnetic storm index was used as a mediator for this study. The observation covers from the year 1901 up to 2015 (i.e. between the 14th and the middle of the 24th solar cycles) for an area that covers the majority of China and its bordering countries. Data for solar activities such as sunspot number and solar wind parameters, including the speed, dynamic pressure and input energy of solar wind, were collected from Solar Influences Data Analysis Center (SIDC) and Advanced Composition Explorer (ACE), respectively. Data for geomagnetic storm indices such as disturbance storm time (DST) index, 3-h planetary index (Kp) and an average of the planetary index (Ap) were obtained from the National Aeronautics and Space Administration (NASA) via OmniWeb Data Explorer and the Space Physics Data Facility. Data number of the earthquake for the small (M<4.9) and large (M>4.9) magnitude in Richter scale were obtained from U.S geological survey database (USGS). The analysis focused on the variation in the number of earthquakes by considering solar wind and geomagnetic storm index based on the ascending and descending phases of each solar cycle. It is found that the number of earthquake occurrences increases during the descending phases of the solar cycle. It is predicted that there will be significantly more number of earthquakes within the next 3 years until 2019.